Odpowiedzi

Najlepsza Odpowiedź!
2010-03-16T19:29:29+01:00
A) 4x-3 = 3x +5
x=8
b) 5x + 2= 7 - 3x
8x=4
x=1/2
c)3 ( x - 1 )=0
3x=3
x=1
d) -6 ( x +1) = 24
-6x-6=24
-6x=30
x=-5
e) -7 ( x -2) = 3x- 1
-7x+14=3x-1
-10x=-15
x=3/2
f) 4( x -1) = 6(1+x)
4x-4=6+6x
-2x=10
x=-5
1 5 1
2010-03-16T19:34:13+01:00
A) 4x-3 = 3x +5 /-3x
x-3=5 /+3
x=8

b) 5x + 2= 7 - 3x /-2
5x=5-3x /+3x
8x=5 /:8
x=0,625

c)3 ( x - 1 )=0
3x-3=0 /+3
3x=3 /:3
x=1

d) -6 ( x +1) = 24
-6x-6=24 /+6
-6x=30 /:6
-x=5
x=-5

e) -7 ( x -2) = 3x- 1
-7x+14=3x-1 /+7x
14=10x-1 /+1
15=10x /:10
1,5=x

f) 4( x -1) = 6(1+x)
4x-4=6+6x /+4
4x=10+6x /-6x
-2x=10 /:2
-x=5
x=-5

:)
1 5 1